2019
DOI: 10.1186/s12879-019-4642-7
|View full text |Cite
|
Sign up to set email alerts
|

American tegumentary leishmaniasis diagnosis using L. (V.) braziliensis fixed promastigotes: a comparative performance of serological tests and spontaneous cure identification

Abstract: BackgroundThe present study aimed to demonstrate the applicability of a flow cytometry-based serology approach to identify spontaneous cure by the detection of immunoglobulin G, and also, the diagnosis and cure criterion by the IgG1 isotype in American Tegumentary Leishmaniasis – ATL caused by L. (V.) braziliensis. Also, a comparison between flow cytometry with the serological conventional technique was performed.MethodsForty five individuals were included in study. They were assessed in two moments: First, 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The frequency of positive anti- Leishmania antibodies was high (in eight of nine patients), especially for IgG1, a Th1-induced IgG subclass. This finding is in accordance with others that showed IgG1 is a promising serologic biomarker for ATL diagnosis [ 26 , 36 ]. On the other hand, the IGRA-Leish results showed that almost half (5 out 9) of the patients had a low capacity to produce IFN-gamma by specific peripheral blood cells, an important effector cytokine induced by Leishmania antigens.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The frequency of positive anti- Leishmania antibodies was high (in eight of nine patients), especially for IgG1, a Th1-induced IgG subclass. This finding is in accordance with others that showed IgG1 is a promising serologic biomarker for ATL diagnosis [ 26 , 36 ]. On the other hand, the IGRA-Leish results showed that almost half (5 out 9) of the patients had a low capacity to produce IFN-gamma by specific peripheral blood cells, an important effector cytokine induced by Leishmania antigens.…”
Section: Discussionsupporting
confidence: 93%
“…Epidemiological surveys to identify people infected with Leishmania are commonly performed through serological tests of low sensitivity, especially for recent infections or for individuals with more than two years of successful cure after CL treatment [ 26 , 36 ]. Surveys based on the detection of the cellular immune response have also been reported [ 37 ], but due to the discontinuation of the MST antigens, this is no longer an available alternative [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the TL, the anti-parasite antibody production is usually lower against Leishmania antigens, mainly in CL cases, and diagnostic tests are not effective to detect the disease [34].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has several advantages for immunoassays, such as high throughput capacity, possibility of analyte quantification, reduced sample volume, high reproducibility and sensitivity (14,15). More importantly, it allows the development of multiplex studies using recombinant antigens, and it can be used as a monitoring tool for cured patients, allowing a more sensitive detection of anti-Leishmania antibodies (16)(17)(18). Therefore, the aim of this study was to evaluate the performance and to verify the possible application of an alternative diagnostic method using flow cytometry to detect anti-L. infantum antibodies in HIVinfected patients.…”
Section: Introductionmentioning
confidence: 99%